The Impact of Deferred Tax Assets, Discretionary Accrual, Leverage, Company Size and Tax Planning Onearnings Management Practices - Widiatmoko, Jacobus; Mayangsari, Ika (Department of Management, Faculty of Economics, Semarang State University, Indonesia, 2016)
The purpose of this study is to analyze and provide empirical evidence of the influence of deferred tax asset, discretionary accrual, leverage, company size, and tax planning on earnings management. Financial performance is an indicator that is required by company management to measure the effectiveness of company performance. This research used secondary data that was got from annual report published in www.idx.co.id and data from Indonesian Capital Market Directory (ICMD). Populations of the research are manufacturing companies listed on Indonesia Stock Exchange from 2011-2013. Samples were selected by using purposive sampling method. There are 208 observations that will examined by logistic regression analysis. The result shows that deferred tax asset has negative and not significant effect to the earnings management, discretionary accrual has negative and not significant effect to the earnings management, leverage has negative and significant effect to the earnings management, company size has positive and significant effect to the earnings management, tax planning has positive and not significant effect to the earnings management.Tujuan penelitian ini menganalisis bukti empiris mengenai pengaruh asset pajak tangguhan, discretionary accrual, leverage, ukuran perusahaan, dan perencanaan pajak terhadap manajemen laba. Kinerja keuangan adalah indikator untuk mengukur efektivitas perusahaan. Penelitian ini menggunakan data sekunder yang diperoleh dari www.idx.co.id serta data dari Indonesian Capital Market Directory (ICMD). Populasi penelitian ini adalah perusahaan manufaktur yang terdaftar di BEI tahun 2011-2013. Sampel dipilih dengan purposive sampling. Terdapat 208 observasi yang akan diuji dengan model analisis regresi logistik. Hasil penelitian ini menunjukkan bahwa asset pajak tangguhan memiliki pengaruh negatif dan tidak signifikan terhadap praktik manajemen laba, discretionary accrual memiliki pengaruh negatif dan tidak signifikan terhadap praktik manajemen laba, leverage memiliki pengaruh negatif dan signifikan terhadap praktik manajemen laba, ukuran perusahaan memiliki pengaruh positif dan signifikan terhadap praktik manajemen laba, perencanaan pajak memiliki pengaruh positif dan tidak signifikan terhadap praktik manajemen laba.JEL Classification: G3, G32